INDIGENOUS FASHION OF SEMIOTIC AT DANI TRIBE IN WAMENA PAPUA HIGHLAND - Manase Halitopo; Napius Kogoya (2024)
Papua Island has many ethnic groups, one of them is Dani tribe which is located in the Highland of Papua Province. The objectives of this research were to recognize the semiotics meaning of the form and size in the Dani tribe. In addition, the researcher took the data from the elders who have grown up and the stakeholders in the Wamena city. In collecting data, the researcher did the observation, interview, and documentation. In analyzing the data, the researcher used the data condensation, data display, and the verifying. Therefore, the result showed that there are some traditional fashion used by men such as Werene Puali (Parrot), Siluki (Fox tail), Kena Esi (Cockatoo feather), Werene Kare (Parrot feather), Hupa Eken (Grain of wheat), Sisika (Eagle feather), Besi (Charcoal of grass), Inyelak Pisik (Yellow clay), Wam Aek (Pork fang), Melaik (Small white tie), Walimo (Long tie), Yalema Esi (The back necklace), Yeke esi (Bracelet), Sege (Spear), Sike (Arrow), Tok eken (Bow), Holim (Water Gourd), and Saniken (Belt) and the women tradition fashion were Sali (Skirt for unmarried women), Yokal (Skirt for marriade women), and Sekan (Bracelet), Inyelak Pisik (Yellow clay), Traditional Bag (Su).